Butterfly diversity (Lepidoptera: Papilionoidea) of Mt. Blegoš and Mt. Koprivnik (Škofjeloško hribovje, Slovenia) - Luka Šturm; Andrej Peternel; Rudi Verovnik (Natura Sloveniae)
An overview of the surveys of butterfly fauna of Mt. Blegoš, Mt. Koprivnik and their surroundings is provided. In 2018, 14 surveys were performed and 80 butterfly species on eight transects recorded in the process. Additional surveys in 2019 and 2020 yielded 5 additional butterfly species. Among the butterflies observed, Parnassius mnemosyne, Lycaena hippothoe, Euphydryas maturna, Euphydryas aurinia, Melitaea britomartis, Melitaea diamina, and Pyrgus alveus are identified as vulnerable species, while both Phengaris arion and Phengaris alcon are classified as endangered species in Slovenia. The latter was found on two occasions in July 2018 and July 2020 on a single locality. Eggs of P. alcon were found on the host plant Gentiana cruciata at the same locality. Despite the fact that many species characteristic of higher altitudes were observed, like Aricia artaxerxes, Pyrgus alveus, Erebia stiria and Lasiommata petropolitana, other, which had still been present a few decades ago, were not found (Parnassius apollo and Boloria pales). In this article, the problem of loss of important butterfly habitats in the region due to overgrowing, and the negative impacts of overgrazing is also highlighted.